KONSEP SERTA IMPLEMENTASI MERDEKA BELAJAR PADA EVALUASI PELAJARAN PENDIDIKAN AGAMA ISLAM - Endang Retnowati; Risnawati Risnawati; Miftahir Rirqa; Nur Azizah (Tasyri’: Jurnal Tarbiyah – Syari’ah Islamiyah, 2025)
This paper plans to decide the impact of the idea of merdeka belajar and its suggestions in the assessment of Islamic Strict Training Learning. This paper utilizes a subjective methodology and writing concentrate on strategies. In light of the consequences of the conversation, assessment comprises of estimation and evaluation. With regards to learning, assessment has a vital and key position, since it is remembered for the learning steps. The point is to decide the adequacy and proficiency of the learning framework. The degree remembers assessment for learning programs, growing experiences, and learning results. By and large, the assessment standards comprise of progression, exhaustive, fair, goal, agreeable, and commonsense. In particular, the standards comprise of lucidness, rationality, teaching method, and responsibility. In light of the writing audit that has been done, the strategy of the Service of Training and Culture, Nadiem Makarim, is known as the "merdeka belajar " strategy. This strategy incorporates 4 things: Ujian Sekolah Berstandar Nasional (USBN) created by each school; the Ujian Nasional (UN) changed to an Asesmen Kompetensi Least (AKM) and a person overview; opportunity of teachers to Rencana Pelaksanaan Pembelajaran (RPP); and adaptability in Penerimaan Peserta Didik Baru (PPDB). Dalah Deka Learning plans to make understudies who are inventive, innovative and in view of local area needs, the universe of work, as well as an extensive evaluation. With respect to in this article, that's what the scientist presumes: the improvement of assessment depends on the motivation behind human creation, which is to turn into a caliph on this planet. Consequently, Islamic Strict Training instructors should have the option to assess the improvement of understudies covering parts of Mental (aqliyah), Full of feeling (qolbiyah), and Psychomotor (amāliyah).